The Study of Emerging Trends of Hospital Occurrence of Surgical Ophthalmic Diseases in Dogs - , Rajasekaran Tiruppur Manikumar; , Shashi Kant Mahajan; , Nameirakpam Umeshwori Devi; , Jasmeet Singh Khosa; , Arun Anand (Archives of Current Research International, 2025)
Aim: To study the emerging trends of hospital occurrence of the surgical ophthalmic diseases in dogs. Place and Duration of Study: Department of Veterinary Surgery and Radiology, College of Veterinary Science, Guru Angad Dev Veterinary and Animal Sciences University, Ludhiana, Punjab, India during the period from October 2020 to March 2021. Methodology: The study was conducted on the dogs presented to the hospital clinics for primary ocular ailments with the objective of reporting the various ocular affections observed in dogs. Results: A total of 141 dogs were studied over a period of six months with the younger dogs most commonly presented for ocular affections than the adult and senile dogs. The incidence of ocular disorders was more in male animals compared to the female animals. Pugs were the most frequently presented breed of dogs for ocular affections followed by Labrador Retriever and Spitz. Bilateral affections were more common than the affections of either right or left eye and cornea was the most commonly affected anatomical structure of the eye followed by the lens and other structures of eye. Conclusion: Pigmentary keratitis, cataract, traumatic proptosis and corneal ulcers were the most common ocular affections observed in more than 50 percent of the study population.